Front cover: Redox modulation of curcumin stability: Redox active antioxidants increase chemical stability of curcumin. Issue 3 (3rd March 2016) - Nimiya, Yoshiki; Wang, Weicang; Du, Zheyuan; Sukamtoh, Elvira; Zhu, Julia; Decker, Eric; Zhang, Guodong
Abstract : Mol. Nutr. Food Res . 2016, 60, 487–494. DOI:10.1002/mnfr.201500681 Co‐addition of redox‐active antioxidants dramatically enhances chemical stability and biological activity of curcumin at physiological pH, suggesting that a redox‐dependent mechanism plays a critical role in mediating curcumin degradation. In addition, curcumin itself, instead of its degradation products, is largely responsible for the observed biological actions of curcumin.